Metodologias de sínteses de nanoestruturas de dissulfeto de molibdênio (MoS2) via rotas top-down e bottom-up e aplicações para remediação ambiental - Schneider, Rodrigo (2022)
The development of nanostructured platforms and nanocomposites has shown potential for applications aimed at pollutants mitigation. Molybdenum disulfide (MoS2) is one of these versatile nanomaterials that can act as pollutant removal agents due to its characteristics such as high surface area, functional groups, chemical stability, thermal stability and 2D structure, having been applied in adsorption systems and filtering systems of dyes of organic and inorganic molecules. However, factors linked to the cost, time required and efficiency of synthesis routes, in view of the proposed environmental applications are challenging. Therefore, in the project new experimental conditions for the bottom-up and top-down syntheses of molybdenum disulfide nanostructures have been proposed, which were combined to produce nanocomposites. By investigating the morphology of each molybdenum disulfide obtained and their characteristics, it was possible to use them in different environmental remediation systems, including dye adsorption, metal adsorption, membrane modification and metal detection. Initially, it was found that different processing routes contribute to the exfoliation process and increase the exposed area of the MoS2 sheets. The top-down synthesis, for example, has the capacity to increase the Pb(II) ion removal efficiency, reaching a capacity of 740.7 mg.g-1. It was also found that the bottom-up route is more advantageous for removing dye (macromolecule) compared to MoS2 synthesized by top-down or unprocessed route, reaching adsorption capacity of 111.2 mg.g-1 of MoS2. When the MoS2 synthesized by the bottom-up route was immobilized on commercial Polysulfone filtration membranes, the membrane efficiency rose from 79% to 99% for rejection of the Direct Red dye and from 76% to 91% for the Congo Red dye. In addition, MoS2 Quantum Dots were obtained with a quantum yielding ranging from 7-13,2% with ability to detect heavy metals ions. Among different ions, Cupper (II) could be detected in laboratory assays in the linear logarithmic range from 1-1000 μM, with detection of <0.38 μM. In general, our results show the potential of the proposed routes to obtain MoS2 of different morphologies and their nanocomposites for applications in environmental remediation.